Psychometric properties of the Children’s Questionnaire of Positive Emotions in Mexican children - Ruvalcaba-Romero, Norma A. (2024)
The present study aims to identify the psychometric properties of the Positive Emotions Questionnaire for girls and boys in the Mexican population. The sample was selected non-randomly and consisted of 668 girls and boys, 4th, 5th and 6th grade elementary school students in public and private schools, whose ages ranged from 8 to 14 years old (M = 10.38; DE = 1.32); 55 % were from the Guadalajara metropolitan area (52 % males and 48% females) and 45 % from the southern area of the state of Jalisco (43 % males and 57 % females). The results obtained from the factorial analysis show adequate fit indexes and the interfactor correlations were moderate, indicating that there is no overlapping of content between the dimensions. The results are discussed, insisting on the creation of promotion, prevention or intervention programs that contribute to the well-being and quality of life of the Mexican child population.